Water-mediated changes in plant–plant and biological soil crust–plant interactions in a temperate forest ecosystem - Pissolito, Clara; Garibotti, Irene Adriana; Varela, Santiago Agustin; Arana, María Veronica; Gonzalez Polo, Marina; Marchelli, Paula; Bruzzone, Octavio Augusto (Copernicus Publications, 2019)
In the quest to understand how biotic interactions respond to climate change, one area that remains poorly explored is how interactions involving organisms other than vascular plants will respond. However the interactions between plants and biological soil crusts (BSCs) are relevant in many ecosystems and they will likely respond uniquely to climate change. Simultaneous considerations of both plant–plant and plant–BSC interactions may substantially improve our understanding of this topic. The aim of this study is to assess whether water availability differentially affects the biotic effects of BSCs and pioneer shrubs on the early life-history stage of tree seedling growth.We conducted a greenhouse factorial experiment with soil surface cover (bare soil, soil covered by a creeping shrub and BSC covered soil) and water regime (control and drought) as factors. We monitored Nothofagus pumilio (a native tree species of ecological and economic relevance) seedling water status and growth as well as changes in soil water content and soil properties. The shrub cover had a positive effect on soil water conservation and on the water balance of seedlings under water stress. However, its effect was negative for seedling growth under both water conditions. The BSC also contributed to soil water conservation and apparently added nutrients to the soil. The net effect of the BSC on seedling growth was negative under full-watering conditions but positive under water stress conditions. This result highlights how the studied biotic interactions, and especially interactions involving BSCs, depend on changes in water availability.